PWE-082 Audit of Barrett's Oesophagus Surveillance in The London Cancer Alliance – Structured Programmes with Dedicated Lists/Databases Improve Prague Scoring and Appropriate Follow Up Intervals. (17th August 2016) - Dunn, JM; Wilson, P; Chatu, S; Collins, C; Gess, M; Hayat, JO; Haycock, A; Hoare, J; Hunt, J; Lean, S; Pee, L; Walker, G; et al.
Abstract : Introduction: The London Cancer Alliance is a group of 17 hospitals in North West and South London serving an estimated catchment area of 5.7 million. We have previously demonstrated that dedicated Barrett's oesophagus (BE) surveillance lists improve dysplasia detection. LCA guidelines recommend dedicated surveillance lists, Prague reporting, dual pathology reporting of dysplasia and follow up intervals similar to national guidelines. Methods: One month 'snap shot' audit of patients undergoing BE surveillance in June 2015. Structure of programme at each site was assessed with questionnaire. All patients undergoing endoscopy for BE were audited using endoscopy reporting software tools. New diagnoses or those referred with dysplasia for endotherapy were excluded. The Prague criteria, dysplasia detection rate and dual pathology reporting were assessed. Analysis was by independent t-tests for continuous variables and chi-squared tests for categorical variables. Results: Responses were received from 13/17 sites. 6/13 ran dedicated surveillance lists and 5/6 had an active surveillance database. Dual pathology reporting for dysplasia was confirmed in 11/13 sites and BSG/LCA guidance adhered to in 12/13. A total of 137 patients underwent surveillance endoscopy. Results are shown in table 1 . There was no difference in the mean number of procedures between sites with dedicated vs. non dedicated lists. Only 4/137 patients were diagnosed with dysplasia, with no significant difference between the 2 groups. Prague classification was significantly higher on dedicated lists (p < 0.0001). There was a significant difference between appropriateness of follow up between centres with active surveillance database vs. those without (p = 0.008). Conclusion: Approximately half the sites in the LCA have dedicated lists and/or active surveillance databases, with statistically significant higher Prague classification rates and appropriate choice of surveillance interval at follow up. These metrics could be adopted at a national level to assess quality of BE surveillance programmes. A larger national audit assessing utility of dedicated lists is warranted. Disclosure of Interest: None Declared